Ethics, Patients, Medical Treatment and Christian Spirituality - Ford, Norman (O Mundo da Saúde, 2007)
The present work aims to present guidelines on developing ethical clinical treatment options, provided the necessary social guarantees are in place to prevent abuses, based both in general ethics — which is more than an attitude based on reason, but also recognizes subjective values as being important, and sees patients necessarily as persons who need to be understood from a subjectcentred approach complemented by a perspective based on rational human nature which is the foundation of a person’s subjectivity — and Christian spirituality, which knows Christians find consolation in their faith in the promised blessed life after death.